Stars, Knots, Dragons and Royal Weddings: Badges of the Houses of Braganza and Savoy in a Nineteenth-Century Portuguese Royal Palace. (2nd October 2018) - Seixas, Miguel Metelo de
Abstract : At the palace of Ajuda – the Lisbon residence of King Luís I of Portugal (1838–1889) and his wife Maria Pia of Savoy (1847–1911) – one of the rooms in the queen's apartments is lined with a damask fabric displaying stars, dragons and knots. At a time when there was a transformation, or even a decline, in the use of royal heraldry, the use of such motives demonstrates how an ancient emblematic system was understood and employed by Queen Maria Pia as an instrument of genealogical self-representation and political visual communication. These emblems, in fact, attempted to revive the medieval badges of the Houses of Braganza and Savoy by showing the historical and symbolic links that united the two lineages. In particular, they highlighted the use of the knot by both dynasties, a shared feature that prefigured the union between the two houses. The commissioning of this fabric was related to other decorative choices in the palace, which also foreshadowed the union of King Luís and Queen Maria Pia, such as the proliferation of historical paintings referring to earlier Braganza and Savoy unions, and the portraits of shared ancestors between the two families. Ultimately, the emblems were used to highlight the prestige of the Portuguese Royal House at a palace that, as the royal residence, was presented as the quintessential symbolic space of the monarchy.